2015
DOI: 10.1021/acs.energyfuels.5b00450
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Stability of Diesel/Biodiesel Fuels Measured by a PetroOxy Device and Characterization of Oxidation Products

Abstract: In the present work, the oxidation stability of diesel, rapeseed (RME), and soybean (SME) fatty acid methyl esters (FAME) and a blend of diesel with 10% (v/v) RME (B10−RME) was studied. Fuel samples were aged in the PetroOxy test device from 383 to 423 K at 7 bar. Experiments were conducted in oxygen excess, and the global kinetic constants were determined. The global kinetic constants for diesel, B10−RME, and RME at 383 K were 7.92 × 10 −6 , 2.78 × 10 −5 , and 8.87 × 10 −5 s −1 , respectively. The oxidation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…1,14 Recent studies assessing the oxidation stability of diesel and biodiesel blends using a PetroOxy device (according to ASTM D7545-14 29 and EN 16091:2011 30 ) have concluded that the addition of 10% FAME (RME) reduced the induction period of the blend by 2.6 times (at 403 K) in comparison with the baseline B0 diesel fuel, indicating that FAME had a significant detrimental effect on the oxidation stability of the fuel. 11 The PetroOxy test exposes the fuel to an elevated temperature in a pressurised oxygen environment and, despite the findings related to the variations in the stability of B0 and B10 fuels, it is not clear whether these differences are also observed in real-world operating conditions within a vehicle fuel injection system. The main direct impact of FAME oxidation on the engine operability is not generally the change in the fuel properties but rather solid deposition.…”
Section: Effect Of Fame On Fuel Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…1,14 Recent studies assessing the oxidation stability of diesel and biodiesel blends using a PetroOxy device (according to ASTM D7545-14 29 and EN 16091:2011 30 ) have concluded that the addition of 10% FAME (RME) reduced the induction period of the blend by 2.6 times (at 403 K) in comparison with the baseline B0 diesel fuel, indicating that FAME had a significant detrimental effect on the oxidation stability of the fuel. 11 The PetroOxy test exposes the fuel to an elevated temperature in a pressurised oxygen environment and, despite the findings related to the variations in the stability of B0 and B10 fuels, it is not clear whether these differences are also observed in real-world operating conditions within a vehicle fuel injection system. The main direct impact of FAME oxidation on the engine operability is not generally the change in the fuel properties but rather solid deposition.…”
Section: Effect Of Fame On Fuel Degradationmentioning
confidence: 99%
“…It also provided flexibility in the operating conditions and offered the possibility to study fuel kinetic oxidation and to perform successive oxidation runs on the same sample. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Bacha et al have investigated that the monitoring of biodiesel oxidative degradation should be mainly conducted by Fourier transform infrared spectroscopy (FTIR); the absorption peak around 1745 cm À1 is due to presence of an ester carbonyl group. 4 Faragun et al have observed that the correlation between concentration and FTIR absorption is highly linear (R 2 above 0.993, in most cases 0.999). 5 Shimamoto & Tubino have studied the presence of conjugated dienes in an oxidized biodiesel using UV-vis spectroscopy and found a positive correlation between the peroxide value and UV absorbance.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is mainly for automotive fuels (ASTM D7545) in order to study the oxidation stability of the component. 13,21−24 RSSOT oxidation provides a fast determination of the amount of oxygen consumed through the measurement of the total pressure inside the autoclave reactor (PetroOxy).…”
Section: Introductionmentioning
confidence: 99%